On speciality of Jordan brackets - Shestakov, I. (Algebra and Discrete Mathematics, 2009)
We conjecture a criterium of speciality for Jordan superalgebras of brackets that generalizes the corresponding criterium for Jordan Poisson superalgebras from [8]. We prove the necessarity condition of the criterium. The question on its sufficiency remains open.